Encephalocraniocutaneous Lipomatosis With Neurocutaneous Melanosis. (June 2014) - Jain, Puneet; Chakrabarty, Biswaroop; Kumar, Atin; Gupta, Neerja; Kabra, Madhulika; Gulati, Sheffali
Encephalocraniocutaneous lipomatosis is a rare neurocutaneous syndrome characterized by classical cutaneous and ocular lesions with central nervous system anomalies. We describe an infant with classical encephalocraniocutaneous lipomatosis characterized by probable naevus psiloliparus, frontal subcutaneous lipomas, ocular limbal dermoids and arachnoid cysts, and ventriculomegaly. He also had giant congenital nevus with leptomeningeal melanosis. This case represents a rare association between encephalocraniocutaneous lipomatosis and neurocutaneous melanosis.